Diversity in Video Lectures: Aid or Hindrance? - Fanguy, Mik; Costley, Jamie; Baldwin, Matthew; Lange, Christopher; Wang, Holly (International Review of Research in Open and Distributed Learning, 2019)
Media diversity within video lectures has been shown to have an effect on students who participate in both flipped classes as well as online courses. While some research claims that content delivered through multiple sources leads to more learning, contrasting research makes the claim that too much media hinders cognitive processing. The present study investigated the effects of varying levels of instructional media delivered to students (n=110) within a flipped scientific writing course to investigate the relationship between higher levels of media diversity and student performance. Results showed that more diversity led to lower levels of performance. It was also found that higher levels of media diversity correlated with higher levels of students’ scanning between different forms of media, possibly contributing to the lower levels of performance. The implications of these results provide insight into the optimal level of media diversity, and on student behavior that can affect learning.